Eksistensi PKn Sebagai Pendidikan Nilai dalam Membangun Karakter Bangsa - SAPUTRA, EDI (TINGKAP, 2012)
This article analyzes the existence of civics education learning as a value education in building the character of the nation. Imple-mentation of character education in schools should be grounded to the basic character values​​, which subsequently developed into the values ​​that better suit the needs, conditions, and school environment itself. Basically, success in life is not determined by a person's knowledge and skills, but also by the ability to manage themselves and others. This suggests that the quality of character education of students are very important to be improved. Character education in schools should begin by giving confidence to students to be able to do positive things in their everyday lives. By implementing the character education, students can become more confident and have good emotional intelligence. Kata Kunci: Eksistensi PKn, Pendidikan Nilai, Karakter Bangsa